2016
DOI: 10.1007/s00192-016-2969-9
|View full text |Cite
|
Sign up to set email alerts
|

German translation and validation of the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire–IUGA revised (PISQ-IR)

Abstract: Introduction and hypothesisCondition-specific sexual questionnaires are essential for clinical trials and important patient-reported outcome measures. The aim of the study was to translate the Pelvic Organ Prolapse/Incontinence Sexual Questionnaire–International Urogynecology Association Revised (PISQ-IR) into German and to clinically validate it in a German-speaking population.MethodsThe translated PISQ-IR was linguistically validated in two rounds of cognitive interviews. The final instrument was psychometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
12
0
7
Order By: Relevance
“…SA-CS, SA-CI) and PFDI-20 scores and ISI. The observed correlations were weak or moderate, which is consistent with the results found for the original version of the questionnaire and other language versions of PISQ-IR, for which the results did not always reach statistical significance [16, 1820]. The Arabic version, with a strong correlation between ISI and NSA-CI and SA-CS scores, is the only exception so far, probably due to a high proportion of women with UI in the investigated population [21].…”
Section: Discussionsupporting
confidence: 83%
“…SA-CS, SA-CI) and PFDI-20 scores and ISI. The observed correlations were weak or moderate, which is consistent with the results found for the original version of the questionnaire and other language versions of PISQ-IR, for which the results did not always reach statistical significance [16, 1820]. The Arabic version, with a strong correlation between ISI and NSA-CI and SA-CS scores, is the only exception so far, probably due to a high proportion of women with UI in the investigated population [21].…”
Section: Discussionsupporting
confidence: 83%
“…49 studies reported on convergent validity of the FSFI-19 (Supplementary Table 3). The FSFI-19 was compared to measures measuring sexual function and satisfaction, 15,17,18,21,23e25,28,29,31,33,37,46,53,55,57,58,60,62,64,67e69,71, 72,74,78,79,92,93 quality of life, 19,92 mental health measures, 20,39 physical functional problems, 20,30,32,34,49,54,66,74,77,81,83,87 relationship quality, 20,39,52 and body image. 35,42,43,56,60 A full list of comparison measures can be found in Supplementary Table 3.…”
Section: Convergent Validitymentioning
confidence: 99%
“…For example, the KHQ developed in the English speaking population with urinary incontinence was validated in the German speaking population of women with urinary incontinence 2005 . Some of the questionnaires will be validated at the same time in different languages as part of a multinational study …”
Section: Discussionmentioning
confidence: 99%